An Emerging Role of Glucagon-Like Peptide-1 in Preventing Advanced-Glycation-End-Product-Mediated Damages in Diabetes - Alessandra Puddu; François Mach; Alessio Nencioni; Giorgio Luciano Viviani; Fabrizio Montecucco (Mediators of Inflammation)
Glucagon-like peptide-1 (GLP-1) is a gut hormone produced in the intestinal epithelial endocrine L cells by differential processing of the proglucagon gene. Released in response to the nutrient ingestion, GLP-1 plays an important role in maintaining glucose homeostasis. GLP-1 has been shown to regulate blood glucose levels by stimulating glucose-dependent insulin secretion and inhibiting glucagon secretion, gastric emptying, and food intake. These antidiabetic activities highlight GLP-1 as a potential therapeutic molecule in the clinical management of type 2 diabetes, (a disease characterized by progressive decline of beta-cell function and mass, increased insulin resistance, and final hyperglycemia). Since chronic hyperglycemia contributed to the acceleration of the formation of Advanced Glycation End-Products (AGEs, a heterogeneous group of compounds derived from the nonenzymatic reaction of reducing sugars with free amino groups of proteins implicated in vascular diabetic complications), the administration of GLP-1 might directly counteract diabetes pathophysiological processes (such as pancreatic β-cell dysfunction). This paper outlines evidence on the protective role of GLP-1 in preventing the deleterious effects mediated by AGEs in type 2 diabetes.